Talking It Out: Political Conversation and Knowledge Gaps in Unequal Urban Contexts. Issue 2 (22nd June 2016) - Smith, Amy Erica
Abstract : In many contemporary urban spaces, political information accrues to high status neighborhoods. This might exacerbate political inequality as the information-rich and information-poor each talk primarily with others like themselves. When information is specific and broadly diffused through the media, however, the convenience and low cognitive costs of everyday conversation could be especially helpful for the disadvantaged. This article shows how political conversations intensify or ameliorate spatial knowledge gaps, using a six-wave panel survey in fifty Brazilian neighborhoods between 2002 and 2006. Multilevel models demonstrate that conversation was more frequent in high education neighborhoods, but had a greater impact on specific, factual knowledge in low-education neighborhoods, leading to shrinking knowledge gaps. However, conversation slightly widened spatial gaps in socially perceived general knowledge.